Traditional Portland cement and MgO-based cement: a promising combination?. (June 2017) - Tonelli, Monica; Martini, Francesca; Calucci, Lucia; Geppi, Marco; Borsacchi, Silvia; Ridi, Francesca
Abstract: MgO/SiO2 cements are materials potentially very useful for radioactive waste disposal, but knowledge about their physico-chemical properties is still lacking. In this paper we investigated the hydration kinetics of cementitious formulations prepared by mixing MgO/SiO2 and Portland cement in different proportions and the structural properties of the hydrated phases formed in the first month of hydration. In particular, the hydration kinetics was investigated by measuring the free water index on pastes by means of differential scanning calorimetry, while the structural characterization was carried out by combining thermal (DTA), diffractometric (XRD), and spectroscopic (FTIR, 29 Si solid state NMR) techniques. It was found that calcium silicate hydrate (C-S-H) and magnesium silicate hydrate (M-S-H) gels mainly form as separate phases, their relative amount and structural characteristics depending on the composition of the hydrated mixture. Moreover, the composition of the mixtures strongly affects the kinetics of hydration and the pH of the aqueous phase in contact with the cementitious materials. The results here reported show that suitable mixtures of Portland cement and MgO/SiO2 could be used to modify the properties of hydrated phases with potential application in the storage of nuclear waste in clayey disposal. Highlights: pH vs. time trends of formulations made of Portland, MgO and SiO2 can be modulated. Low amounts of PC in MgO/SiO2 mixtures accelerate and enhance M-S-H precipitation. Low amounts of MgO/SiO2 in PC mixtures accelerate and enhance C-S-H precipitation. M-S-H forms in mixtures whose pH is higher than that previously reported as ideal.